Новые палеарктические роды сцелионид (Hymenoptera, Scelionidae) фауны СССР - Козлов, М.А.; Кононова, С.В. (Вестник зоологии, 1985)
Morphological characteristic of the genera Opisthacantha Ashmead and Paridris Kieffer, formerly unknown in the USSR territory, is given. Two species are described as new: C. atrata sp. n. and P. leda sp. n. Type-material is deposited in collections of Schmalhausen Institute of Zoology, Kiev, and Zoological Institute, Leningrad.